Explore London - Hutchison, Patricia (Great cities of the world (12 Story Library (Firm)), 2020)
Provides information about London, England, and its climate, history, economy, infrastructure, and culture. Features information about architecture, transportation, and popular tourist attractions in the city. Includes color photographs, fact boxes, a map, a glossary, and resources for further learning.